Synthesis of Orange Colored Silica Gel Based on Rice Husk Ash by Using Iron Salt Indicator - Pooneh Abachi; Reza Khoshbin; Ramin Karimzadeh (Journal of Chemical and Petroleum Engineering)
Silica gel is a solid adsorbent known for its unique property of changing color as it adsorbs moisture. The main component in the production of silica gel is sodium silicate, which can be derived from natural raw materials such as sugarcane bagasse ash, rice husk ash and coconut shell. In this study, sodium silicate was extracted from rice husk ash (RHA), followed by the synthesis of silica gel using the sol-gel method. The resulting silica gel was then colored orange using iron (ⅠⅠⅠ) chloride salt. FE-SEM image showed a homogeneous distribution of particle size and color on the surface of the silica gel. The BET surface area of orange silica gels synthesized from commercial sodium silicate and RHA (Aging time = 24 hours) was found to be 248.6 and 179.86 m2/gr, respectively but the high Smeso/Smicro in silica gel from rice husk ash contributes to its suitable moisture adsorption capacity compared to silica gel from industrial sodium silicate.